Event spaces and the shaping of economic subjectivity: Inside the Social Enterprise World Forum. (August 2021) - Baker, Tom; Jones, Ryan; Mann, Michael; Lewis, Nick
Drawing on observations at the 2017 Social Enterprise World Forum (SEWF) – a global conference held in Christchurch, New Zealand – this paper examines the significance of localised event spaces in shaping economic subjects and, by extension, economic sectors. Conferences such as the SEWF are sites and moments that provide access to new knowledge, foster collective action and shape the subjectivities of economic actors. We describe how the SEWF cultivated sympathetic affective responses towards social enterprise and the subject position of the social entrepreneur, and demonstrate how the local specificities of Christchurch, as a place, were key to the cultivation of social-entrepreneurial subjectivity at the SEWF.